Las leyes de Israel: democracia teórica y racismo practico - Qasem Alshboul, Ayman Mohammed (Nómadas. Critical Journal of Social and Juridical Sciences, 2006)
The essence of this investigation depends on analyzing the decreed laws imposed by the state of Israel basing on cases of real live studies. The content of these Israelis laws are inspired by three sources: the Jewish religion, the Zionism and the concepts and liberal principles. The Zionism as an ideology and international movement plays an important role in determining the content of the laws Israelis, most of its content confirms the racist essence of the Zionist State in it persecution form and political oppression and, in the racial discrimination against the legitimate and autochthonous proprietors of all non Jews.